2014
DOI: 10.3171/2014.7.jns13594
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of hand function in C7–T1 brachial plexus palsies using a staged approach with nerve and tendon transfer

Abstract: Brachial plexus palsies of C7-T1 result in the complete loss of hand function, including finger and thumb flexion and extension as well as intrinsic muscle function. The task of reanimating such a hand remains challenging, and so far there has been no reliable neurological reconstructive method for restoring hand function. The authors aimed to establish a reliable strategy to reanimate the paralyzed hand. Two patients had sustained C7-T1 complete lesions. In the first stage of the operative procedure, a supina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…In our study, we required nerve grafts to anastomose the brachioradialis branch to the PIN, and the brachioradialis could usually be used to reconstruct the intrinsic muscle function. 13 The extensor carpi radialis longus branch could usually be directly anastomosed to the PIN in the present investigation, but this procedure may influence wrist extension, because the extensor carpi ulnaris is paralyzed and the carpi radialis brevis is partially impaired in C7 À T1 palsy. In a patient with several extensor carpi radialis longus branches, it is possible to use one branch to repair the PIN, with less damage to wrist extension.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, we required nerve grafts to anastomose the brachioradialis branch to the PIN, and the brachioradialis could usually be used to reconstruct the intrinsic muscle function. 13 The extensor carpi radialis longus branch could usually be directly anastomosed to the PIN in the present investigation, but this procedure may influence wrist extension, because the extensor carpi ulnaris is paralyzed and the carpi radialis brevis is partially impaired in C7 À T1 palsy. In a patient with several extensor carpi radialis longus branches, it is possible to use one branch to repair the PIN, with less damage to wrist extension.…”
Section: Discussionmentioning
confidence: 84%
“…Through this strategy, patients with C7-T1 brachial plexus palsies have recovered finger flexion, finger extension, and thumb opposition, which has led to successful grasping and pinching motions. 13 However, finger flexion strength after brachialis mo-tor branch transfer has only corresponded to Medical Research Council (MRC) Grades M2-M3, lowering the grip strength and practical value of the reconstructed hand. We determined that the need for finger flexion strength was greater than the need for finger extension to ensure grasp strength and stability; thus, finger flexion achieved solely through brachialis motor branch transfer is not sufficient.…”
mentioning
confidence: 99%
“…Some authors have reported their clinical results with this nerve transfer. 5 11 22 23 24 Dong et al 5 transferred the motor branch from the radial nerve to the supinator muscle to the PIN in four patients. These patients were followed-up and evaluated every three to four months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…These authors performed such transfer in 10 patients, from which 9 recovered at least M3 muscle strength (full range of motion overcoming gravity and small resistance). Zhang et al 22 transferred one supinator branch to the PIN in two patients. They reported that this procedure proved to be reliable, effective, and quick in restoring finger and thumb extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation